Personal Branding Strategies for Radio Broadcasters in the Digital Era: A Qualitative Analysis - Harlita Nindhasari; Harliantara, Harliantara; Zulaikha; Nurannafi FSM; I Made Sutika (Technium Social Sciences Journal, 2025)
The proliferation of digital media has significantly impacted the radio industry, necessitating broadcasters to adapt their strategies to maintain relevance and competitiveness. This study investigates the significance of personal branding for radio broadcasters in the digital era, identifies efficacious strategies for audience engagement, and establishes a robust online presence. Through a comprehensive review of scholarly literature and industry reports, this research elucidates the key elements of successful personal branding, including the development of a unique value proposition, creation of compelling content, and utilization of digital platforms such as social media, podcasts, and personal websites. The findings underscore the critical role of consistency, authenticity, and engagement in establishing trust and credibility with the audience. Furthermore, the study examines the advantages of collaborating with influencers and industry partners to expand reach and enhance personal brands. As the media landscape continues to evolve, radio broadcasters must invest in personal branding to differentiate themselves, demonstrate their expertise, and cultivate a loyal following. This study contributes to the field of communication science and provides valuable insights for radio broadcasters seeking to thrive in the digital era through the development of effective personal branding strategies.